The intersection of financial toxicity and family building in young adult cancer survivors. Issue 16 (20th June 2018) - Thom, Bridgette; Benedict, Catherine; Friedman, Danielle N.; Kelvin, Joanne F.
Abstract : Financial toxicity and family‐building difficulties may co‐occur in young adult cancer survivors. Herein, the authors describe this intersection and propose steps to alleviate associated distress.